Education Level and Employment Status Correlated with Parenting Patterns in Pre-School Age Children - Maratus Sholichah Fitriah Hajar Kusnianto; Handayani; Zakia Fikriana (STIKes Patria Husada Blitar, 2024)
Parenting is the attitude of parents to their children seen from their correlation, giving rules to children, how to give attention and respond to children's desires. This is the initial education received by children in the family environment. This study aimed to analyze the correlation between the level of education and the employment status of parents with parenting patterns of preschool children. This research was a quantitative, correlation research. The population based on inclusion criteria was parents who had children aged 3-6 years, willing to become respondent, and presented at Dahlia Posyandu activities. The exclusion was parents who did not complete the questionnaire and did not biological parents who attended the activities. The respondent sample was taken using a purposive sampling technique of 34 people which was carried out on July 1 - July 31, 2023. The Instrument used Parental Authority Questionnaire (PAQ). The data analysis was carried out using the Spearman Correlation test. The results obtained there was a correlation between education level and employment status with parenting patterns. Parents are expected to be able to apply good parenting patterns, namely supporting children to become independent, getting used to having discussions with children in everyday life.